For a New Global Labour History: A View from Eastern Europe - Cucu, Alina-Sandra (Historein, 2020)
This article investigates the recent attempts to integrate Eastern Europe in global labour history as a unique opportunity to formulate an intellectual agenda that would place the region on the global map, but on its own analytical terms. Based on two interconnected research projects on industrial labour in socialist Romania, it argues that these integration efforts have to start with a systematic endeavour to bring labour history and the history of capital formation in the region together. The endeavour of articulating a truly global labour history from a specifically Eastern European angle requires us to reconsider the scale(s) at which we construct our narratives, moving away from an epistemological perspective that favours eventful fractures and towards a processual analysis of labour in the region.